Are medical comorbid conditions of bipolar disorder due to immune dysfunction?. (13th March 2015) - Rosenblat, J. D.; McIntyre, R. S.; Leboyer, Marion
<x xml:space="preserve">Abstract</x> Objective Epidemiological data have shown a clear association between bipolar disorder (BD) and medical comorbidities. The aim of this article was to assess the evidence of immune dysfunction as a key mediator of this observed association. Method For this narrative clinical overview, the MEDLINE/PubMed, EMBASE, Google Scholar, and ClinicalTrials.gov databases were searched for relevant articles. Results Bipolar disorder has been shown to have an increased prevalence in patients with autoimmune disorders, cardiovascular disease, and metabolic dysfunction. Further, an elevation in proinflammatory cytokines in BD has been repeatedly demonstrated. Several mechanisms have been proposed to explain the effect of immune dysfunction on mood and cognition. Anti‐inflammatory agents including TNF‐α inhibitors, non‐steroidal anti‐inflammatory drugs (NSAIDs), minocycline and omega‐3 polyunsaturated fatty acids (O3PUFA) are being investigated for their use as novel treatment of BD in patients with immune dysfunction. Conclusion Immune dysfunction appears to be an important mediator of the association observed between BD and medical comorbidities. It therefore serves as a potential novel target for treatment of BD. Further, the observed bidirectional interaction merits screening for psychiatric disorders in patients with immune dysfunction and vice versa to allow for early detection and treatment of this at risk population.